THE ROLE OF AKIDAH AKHLAK TEACHERS IN BUILDING THE RELIGIOUS CHARACTER OF STUDENTS IN THE CHALLENGES OF THE 21ST CENTURY AT MADRASAH ALIAH NEGERI 2 POLEWALI, MATAKALI DISTRICT, POLEWALI MANDAR REGENCY - Sudirman, Sudirman; Nurzamsinar, Nurzamsinar; Ahmad, Najamia (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
The problems studied in this research are: (1) What is the role of moral belief teachers in shaping the religious character of students in the challenges of the 21st century at MAN 2 Polewali, Matakali District, Polewali Mandar Regency? (2) What are the supporting and inhibiting factors for moral belief teachers in shaping the religious character of students in the challenges of the 21st century at MAN 2 Polewali, Matakali District, Polewali Mandar Regency? This type of research is called qualitative research. Data collection was carried out by conducting observations, questionnaires and documentation. Analyse the data by carefully considering the data that has been collected, and then the data is concluded. Research results from the role of moral aqidah teachers in shaping the religious character of students in the challenges of the 21st century at MAN 2 Polewali, Matakali District, Polewali Mandar Regency, are to exemplify good habits, examples that are worth emulating, instilling an attitude of tolerance, joining an organisation that is in line with what is taught by madrasa. Factors that support and strengthen character education are the role of parents and the environment, the role of madrasas and organisations that students join. Factors that become obstacles to improving and developing the character of students are the differences in the character of different children and the impact of increasingly sophisticated and rapidly developing conditions or circumstances, increasing modern lifestyles, morals, culture and personality